Enhancing Dietary Knowledge And Low-Salt Compliance In Hypertension Patients Through Flip Chart-Based Nutritional Literacy - Zahara, Ayu; Simbolon, Demsa; Yunita, Yunita (Poltekkes Kemenkes Semarang, 2024)
Hypertension is a non-communicable disease where blood pressure is above the normal limit, namely systolic â‰¥140 mmHg and diastolic â‰¥90 mmHg. Hypertension is often known as the